H3K4 acetylation, H3K9 acetylation and H3K27 methylation in breast tumor molecular subtypes - KARSLI, SEHER (FUTURE MEDICINE LTD, 2016)
Aim: Here, we investigated how the St Gallen breast molecular subtypes displayed distinct histone H3 profiles. Patients & methods: 192 breast tumors divided into five St Gallen molecular subtypes (luminal A, luminal B HER2-, luminal B HER2+, HER2+ and basal-like) were evaluated for their histone H3 modifications on gene promoters. Results: ANOVA analysis allowed to identify specific H3 signatures according to three groups of genes: hormonal receptor genes (ERS1, ERS2, PGR), genes modifying histones (EZH2, P300, SRC3) and tumor suppressor gene (BRCA1). A similar profile inside high-risk cancers (luminal B [HER2+], HER2+ and basal-like) compared with low-risk cancers including luminal A and luminal B (HER2-) were demonstrated. Conclusion: The H3 modifications might contribute to clarify the differences between breast cancer subtypes.
Keywords: breast cancer; H3 modifications; St Gallen molecular subtypes; INTERNATIONAL EXPERT CONSENSUS; HISTONE MODIFICATIONS; DNA HYPERMETHYLATION; DEVELOPMENTAL GENES; CANCER HIGHLIGHTS; BRCA1 EXPRESSION; PRIMARY THERAPY; ESTROGEN; ASSOCIATION; HER-2/NEU